Penderia pH Berkomputer Menggunakan Gentian Optik - Ahmad, Sahrim; Ahmad, Musa; Kok Long, Wong (Universiti Putra Malaysia Press, 1996)
This paper discusses the development of a pH sensor using optical fibre. Optical fibre was used to guide light from the light source, LED, to the probe and eventually to a photodetector, i.e. solid state photodiode. A few drops of phenolptalin were added to the solution before the measurement was made. This sensor can be used for acid-base titration. The sensor was interfaced to a personal computer to facilitate the data retrieval process.